Effects of different ventilation strategies on exhaled nitric oxide in geriatric abdominal surgery. (26th February 2015) - Cui, Yinghua; Pi, Xin; Wang, Changsong; Liu, Shujuan; Gong, Yulei; Wang, Yang; Zhang, Fan; Shi, Jinghui; Lin, Ziwei; Zhang, Xin; Li, Enyou
Abstract: Exhaled nitric oxide (eNO) has been suggested to be a marker of small airway injury. We investigated the effects of different ventilation strategies on eNO. Sixty-nine patients who received elective open abdominal surgery under general anesthesia with more than 2 h of surgery duration were randomly divided into three groups: high tidal volume of 10–12 ml kg −1 predicted body weight (PBW) with zero end-expiratory pressure (ZEEP) (high V T + ZEEP group); low tidal volume of 6–8 ml kg −1 PBW with 8 cm H2 O positive end-expiratory pressure (PEEP) (low V T + PEEP group); and low tidal volume of 6–8 ml kg −1 PBW with 8 cm H2 O PEEP and recruitment maneuvers (low V T + PEEP + RMs group). eNO, respiratory system compliance (Crs), oxygenation index, inflammatory mediators tumor necrosis factor-alpha (TNF- α ), interleukin-1 β (IL-1 β ), IL-8, prostaglandin E2 (PGE2) and PGF2 a as well as pulmonary function were measured during the perioperative period. The postoperative eNO decreased in 78.3% of patients in the high V T + ZEEP group and low V T + PEEP group, and increased in 56.5% of patients in the low V T + PEEP + RMs group ( P = 0.016). The Crs level in the high V T + ZEEP group significantly decreased with time but significantly increased in the low V T + PEEP + RMs group ( P  < 0.05). The oxygenation index, inflammatory mediators and pulmonary function did not statistically differ among the three groups. Compared with the low V T + PEEP + RMs group, the decreasing rate of postoperative eNO in the high V T + ZEEP and low V T + PEEP groups was higher, which may imply small airway injury during geriatric abdominal surgery.